Immunohistochemical assessment of E-cadherin and beta-catenin in trichofolliculomas and trichoepitheliomas - Bezděková, Michala; Brychtová, Svetlana; Sedláková, Eva; Steigerová, Jana; Hlobilková, Alice; Bienová, Martina; Kučerová, Renata; Brychta, Tomáš; Krejčí, Veronika; Kolář, Zdeněk (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2007)
BACKGROUND: Trichofolliculomas and trichoepitheliomas are benign skin neoplasms originating from hair follicle cells. They result from defects in the signaling pathways that regulate hair follicle morphogenesis and regeneration. Thus they seem to be an excellent model of these processes. It is known that the E-cadherin/beta-catenin system of adhesion molecules plays a crucial role in the maintenance of tissue architecture. AIM: The aim of the present study was to investigate their involvement in benign hair follicle tumor development. METHODS: Semiquantitative intensity of expression were examined in formalin-fixed and paraffin-embedded tissue sections of 53 trichoepitheliomas, 15 trichofolliculomas and 19 normal skin samples by indirect immunohistochemistry. RESULTS: The intensity of E-cadherin/beta-catenin expression in tumor cells did not differ from controls. However, normal hair follicles cells exhibited membranous E-cadherin/beta-catenin expression, whereas both types of tumors, particularly trichoepitheliomas, showed E-cadherin/beta-catenin expression with a predominantly cytoplasmic localization. CONCLUSIONS: We suggest that this dystopic distribution of the E-cadherin/beta-catenin complex in hair follicle tumor cells may be a marker of cell-cell adhesion disruption which may contribute to the tumor formation.
Keywords: imunohistochemie; beta-katenin; nádory kůže; Cadherins; Hair Diseases; Immunohistochemistry; lidé; bazocelulární nádory; Neoplasms, Basal Cell; kadheriny; nemoci vlasů; Skin Neoplasms; beta Catenin; Humans